PERBAIKAN WAKTU SET-UP DENGAN MENGGUNAKAN METODE SMED PADA MESIN FILLING KRIM - Feby Nurhadiyanto Arief (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
PT. GP is a pharmaceutical company producing pharmaceuticals in solid, semi-solid and liquid form such as   creams and ointments. PT GF has problem in set up time and stop by touble machine during the process   running caused inefficien time.  This problem need improvement action so that company could go running more effecient. The purpose of this research is to get appropriate action and method for reducing the set up time by SMED (Single Minute Exchange of Dies mehod).  SMED applied by separating the activity set up into two stages of the internal set up and external set up.  SMED succesfully decrease in set up time of 26%.